Development of an Indonesian Language E-Learning Platform Based on Islamic Values through Gamification Technology - M. Iqbal Tawakkal; Sahri Sahri; Cecilia Putri Singkuku; M. Zaka Alfarisi (Jurnal Pendidikan Edutama, 2026)
This study aims to develop an Indonesian-language e-learning platform integrated with Islamic values, using gamification to enhance student engagement and meaningful learning in the digital era. The research employed a research and development approach using the ADDIE model, including analysis, design, development, implementation, and evaluation. Needs analysis involved Indonesian language teachers and students to identify learning challenges and integration opportunities. The developed platform provides interactive materials, gamified quizzes, discussion forums, and automated feedback. Expert validation results show high validity, with an average feasibility score of 87.2%, while practicality testing indicates a convenient category, with a user response score of 88.8%. The novelty lies in the systematic integration of gamification and Islamic values within an ADDIE-based Indonesian language e-learning platform.